The Reality and Challenges of Gender Issues in the Tourism Industry - Andilolo, Imanuella R.; Ranteallo, Ikma Citra; Widiana, Harmi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
Tourism industry is still marred with “glass ceiling” phenomenon even though women contribute a significant portion of the overall industry. Women remain underrepresented in top culinary roles and continue to encounter challenges including wage inequality, restricted career advancement, workplace harassment, and deeply rooted patriarchal practices within the professional kitchen. Historically a woman’s place was considered to be in the kitchen. The feminist movement in 1970s opened up opportunities for women to join the work force. However, after decades, women still have difficulty entering the professional kitchen where men continue to dominate. This paper conducts an empirical research on the gender of Head Chefs or Executive Chefs of several five and four-star hotels in Lombok, Indonesia, and discusses challenges on gender issues within the professional kitchen. This paper examines the managerial and social barriers based on gender bias/inequality in professional kitchens; it looks at how female chefs socially manoeuvre within the kitchen culture; and attempts to compile solutions.